1992
DOI: 10.1111/j.1540-8183.1992.tb00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Balloon Coarctation Angioplasty: Long‐Term Results

Abstract: One hundred and ten patients, age 2 days to 35 years (mean 7.0 +/- 7.0 years), have undergone 118 percutaneous balloon angioplasty procedures for discrete coarctation of the aorta since April 1982. The mean systolic gradient was significantly decreased from 48 +/- 22 to 8 +/- 7 mmHg after angioplasty (P less than 0.0001). Long-term results were evaluated in 95 patients, by follow-up catheterization in 30 and Doppler echocardiography in 65 patients. The follow-up period was 1-9 years (4.2 +/- 2.1). At follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Aneurysm formation at the dilation site has remained a long-term concern. Although early studies by Cooper et al (25) and Brandt et al (26) reported high incidence of aneurysm formation, most investigators have reported aneurysm formation incidence varying between 1.8% to 6% (12)(13)(14)27,28), which is consistent with our result (7.8%). No aneurysms were encountered by Koerselman et al (17) and Walhout et al (19).…”
Section: Discussionsupporting
confidence: 95%
“…Aneurysm formation at the dilation site has remained a long-term concern. Although early studies by Cooper et al (25) and Brandt et al (26) reported high incidence of aneurysm formation, most investigators have reported aneurysm formation incidence varying between 1.8% to 6% (12)(13)(14)27,28), which is consistent with our result (7.8%). No aneurysms were encountered by Koerselman et al (17) and Walhout et al (19).…”
Section: Discussionsupporting
confidence: 95%
“…We [15•,19•,37] and others [16] recommend repeat balloon dilatations in such cases, whereas still others [38] prefer surgical intervention.…”
Section: Recoarctationmentioning
confidence: 95%
“…There is scanty data on long-term followup after balloon angioplasty of native Coarctation [44,55,56]. Despite the problems of recoarctation and aneurysms, some requiring repeat intervention at intermediate-term follow-up, the long-term follow-up results (5 to 9 years) appear encouraging in that there was minimal incidence of late recoarctation and no late aneurysm formation.…”
Section: Long-term Follow-upmentioning
confidence: 99%